2022
DOI: 10.3389/fphy.2022.915441
|View full text |Cite
|
Sign up to set email alerts
|

A multilayer network model for studying the impact of non-pharmaceutical interventions implemented in response to COVID-19

Abstract: Non-pharmaceutical interventions (NPIs) are essential for the effective prevention and control of the COVID-19 pandemic. However, the scenarios for disease transmission are complicated and varied, and it remains unclear how real-world networks respond to the changes in NPIs. Here, we propose a multi-layer network combining structurally fixed social contact networks with a time-varying mobility network, select the COVID-19 outbreak in two metropolitans in China as case studies, and assess the effectiveness of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Big data can be used to understand patterns and trends in human mobility, which can inform public health and transportation policies. For example, big data can be used to identify high-risk areas for the spread of infectious diseases and to optimize the distribution of healthcare resources [66][67][68]. vi.…”
Section: Novel Research Frontiers Of Big Data Epidemic Control For Fu...mentioning
confidence: 99%
“…Big data can be used to understand patterns and trends in human mobility, which can inform public health and transportation policies. For example, big data can be used to identify high-risk areas for the spread of infectious diseases and to optimize the distribution of healthcare resources [66][67][68]. vi.…”
Section: Novel Research Frontiers Of Big Data Epidemic Control For Fu...mentioning
confidence: 99%
“…Many predictive epidemiological models have been established prior to or during the outbreak of COVID-19 ( Ciufolini & Paolozzi, 2020 ; Dehning et al, 2020 ; Dowd et al, 2020 ; Enserink & Kupferschmidt, 2020 ; S. Guo et al, 2020 ). The experiences and conclusions from the models are in consensus: reliable short-term prediction is the key to the success of combatting the spread, flattening the curve especially in the initial stages of the spread, regardless of where the prediction was made and how it was made ( Baker et al, 2020 ; Chen et al, 2022 ; Ciufolini & Paolozzi, 2020 ; Davies et al, 2020 ; Dayaratna et al, 2022 ).…”
Section: Introductionmentioning
confidence: 97%
“…Data-driven network-based models were frequently combined with machine learning and deep learning techniques to uncover important patterns and conclusions in specific geographical districts ( Anno, Hirakawa, Sugita, & Yasumoto, 2022 ; Ojugo & Nwankwo, 2021 ; Pinheiro, Galati, Summerville, & Lambrecht, 2021 ; Roy, Biswas, & Ghosh, 2021 ). Another common modeling method that has been used in epidemiological studies is agent-based modeling ( Chen et al., 2022 ; Patel et al., 2021 ; Vedam & Ghose, 2022 ). It represents a detailed description of contagions spread by tracing agents (individuals) and can be highly adjustable to include different nonpharmaticual interventions and assess their relative effects.…”
Section: Introductionmentioning
confidence: 99%
“…It represents a detailed description of contagions spread by tracing agents (individuals) and can be highly adjustable to include different nonpharmaticual interventions and assess their relative effects. A former study ( Chen et al., 2022 ) proposed a multi-layer network that considers both social contact (using an agent-based approach) and urban commuting (using a time-varying network). Employing available vaccine cases, the study examined several control strategies individually and reported their effectiveness.…”
Section: Introductionmentioning
confidence: 99%